The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1039/c9fo02491c
|View full text |Cite
|
Sign up to set email alerts
|

Calcium relieves fluoride-induced bone damage through the PI3K/AKT pathway

Abstract: Bone is the main target of fluorosis, and it has been perfectly elaborated that a moderate dosage of calcium (Ca) can alleviate bone fluorosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…In the F+SeII group, SeNPs decreased p-STAT3 protein expression not following the established trend of p-JAK2, which may be related to the more target proteins. Regarding the p-STAT3, although it is an essential downstream substrate of p-JAK2, it can be influenced by the other signaling pathway such as receptor tyrosine kinase (RTK), and the activation of RTK may lead to JAK-independent tyrosine phosphorylation of STAT. , As for the expression levels of JAK2 and STAT3, they showed an opposite trend with corresponding phosphorylated proteins, which was consistent with our previous experimental results of PI3K and AKT . F induced a decrease in the expressions of JAK2 and STAT3 and increased expressions of p-JAK2 and p-STAT3, while SeNPs supplementation inhibited the harmful effects of F on them.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In the F+SeII group, SeNPs decreased p-STAT3 protein expression not following the established trend of p-JAK2, which may be related to the more target proteins. Regarding the p-STAT3, although it is an essential downstream substrate of p-JAK2, it can be influenced by the other signaling pathway such as receptor tyrosine kinase (RTK), and the activation of RTK may lead to JAK-independent tyrosine phosphorylation of STAT. , As for the expression levels of JAK2 and STAT3, they showed an opposite trend with corresponding phosphorylated proteins, which was consistent with our previous experimental results of PI3K and AKT . F induced a decrease in the expressions of JAK2 and STAT3 and increased expressions of p-JAK2 and p-STAT3, while SeNPs supplementation inhibited the harmful effects of F on them.…”
Section: Resultssupporting
confidence: 88%
“…57,58 As for the expression levels of JAK2 and STAT3, they showed an opposite trend with corresponding phosphorylated proteins, which was consistent with our previous experimental results of PI3K and AKT. 59 F induced a decrease in the expressions of JAK2 and STAT3 and increased expressions of p-JAK2 and p-STAT3, while SeNPs supplementation inhibited the harmful effects of F on them. Moreover, IL-6 is not only the target gene of p-STAT3 but also the major stimulator of p-STAT3, which is verified by our experimental results, which showed that 0.5 and 1 mg Se/kg BW/day SeNPs reduced the elevation of IL-6 and p-STAT3 in a dose-dependent manner.…”
Section: Protective Effects Of Senps On the Basal Metabolic Index In ...mentioning
confidence: 91%
“…The main symptoms of the disease are only fragments of the damage, however. As the study of skeletal fluorosis has been thorough, the deleterious effects of fluoride on bone are well known (Wang et al, 2019b(Wang et al, , 2020. The main performance for osteoblast numbers increases mast cell body, which is the basis for extensive cell damage and apoptosis (Ravanan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The binding of FOXO1 acetylation to ATG7 promotes autophagy for cell survival to resist OS [ 23 ]. FOXO1 in the nucleus increases the translation of B-cell lymphoma-2-like protein 1(BIM) to promote apoptosis [ 24 , 25 ]. The levels of ROS affect FOXO cytoplasmic/nuclear shuttling, FOXO stability, and eventually transcription of FOXO-controlled target genes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%